Parameter Optimization of Customized FDM 3D Printer Machine for Biocomposite Material [Sago/PMMA] Using 2k Fractional Factorial Design - Ibnu Abdul Rosid; Alva Edy Tontowi (OPSI, 2021)
Bone fracture caused by various incident causes medical problems. Then bone restoration is required. Bone grafts can be used to solve this problem. One of the materials that can be used to produce bone graft is PMMA. PMMA requires to be combined with other materials to extend the solidification time. The material that can be used for bone graft material is sago starch. The main ingredient composition of Biocomposite [sago/PMMA] consists of sago: PMMA = 1 : 1 (w/w). The composition of the addition of MMA is 10% (v/w) of PMMA, this is to extend the curing time. Thus the material can be through from the chamber extruder to the nozzle. This research aims to obtain  combinations of 3D Printer FDM Customized machine parameters for minimizing of error dimension. The 3D Printer machine uses pneumatic system to push the material from the container to the chamber and used screw extruder to push the material out through the nozzle. The experimental design method used a 2k fractional factorial design, with 3 parameters, 2 levels and 3 responses. The experimental results obtained that the layer height parameter has a significant influence on the x-dimensional error. The optimization results obtained a combination of parameters to get the smallest error dimensions, the print speed is 25 mm/s, the layer height is 2.93 mm and the fill density is 20%. The results of optimization obtained that the x-dimensional error is 0.016, the y-dimensional error is 0.069 and the z-dimensional error is 0.4539.